2006
DOI: 10.1097/01.brs.0000238968.82799.d9
|View full text |Cite
|
Sign up to set email alerts
|

Pseudarthrosis in Long Adult Spinal Deformity Instrumentation and Fusion to the Sacrum: Prevalence and Risk Factor Analysis of 144 Cases

Abstract: The overall prevalence of pseudarthrosis following long adult spinal deformity instrumentation and fusion to S1 was 24%. Thoracolumbar kyphosis, osteoarthritis of the hip joint, thoracoabdominal approach (vs. paramedian approach), positive sagittal balance > or = 5 cm at 8 weeks postoperatively, older age at surgery (older than 55 years), and incomplete sacropelvic fixation significantly increased the risks of pseudarthrosis to an extent that was statistically significant. Scoliosis Research Society 24 outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
241
3
14

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 375 publications
(261 citation statements)
references
References 12 publications
3
241
3
14
Order By: Relevance
“…The hardware employed, if correctly positioned, provides an immediate primary stability; however, it is not able to bear alone the physiological load to which the spine is subjected and if bone fusion is not achieved the hardware fails. The success of the spine fusion depends on many factors, some related to the patient (age, smoking, previous spine surgery, thoracolumbar kyphosis, coexistence of hip osteoarthritis) [17], other related to the surgical treatment, among them the choice of bone graft or bone graft substitutes having adequate osteogenic, osteoinductive and osteoconductive properties. Autograft, in particular iliac crest bone graft, is considered the gold standard for bone fusion.…”
Section: Discussionmentioning
confidence: 99%
“…The hardware employed, if correctly positioned, provides an immediate primary stability; however, it is not able to bear alone the physiological load to which the spine is subjected and if bone fusion is not achieved the hardware fails. The success of the spine fusion depends on many factors, some related to the patient (age, smoking, previous spine surgery, thoracolumbar kyphosis, coexistence of hip osteoarthritis) [17], other related to the surgical treatment, among them the choice of bone graft or bone graft substitutes having adequate osteogenic, osteoinductive and osteoconductive properties. Autograft, in particular iliac crest bone graft, is considered the gold standard for bone fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Screws in S2 were used to augment the lumbopelvic fixation in the patient with osteoporotic bone cases with revision and subsequent surgeries indicated in one-quarter of patients treated [9,10,13,34,40,44]. Risk factors for failure were elucidated in a report on 144 patients by Kim et al [27]: Besides a thoracolumbar kyphosis and osteoarthritis of the hip, positive postoperative sagittal balance of 5 cm or more, age [55 years, and Explanation of failure in a the patient experienced recurrent sagittal imbalance due to an incomplete correction of the spino-pelvic alignment. In the first revision surgery lumbar lordosis was corrected from kyphosis (left) to slight lumbar lordosis (middle).…”
Section: Discussionmentioning
confidence: 99%
“…However, fixation failures have frequently been reported [10,12]. Many studies have demonstrated a correlation between bone mineral density (BMD) and the strength of pedicle screw fixation [5, 7-9, 11, 17, 20, 22].…”
Section: Introductionmentioning
confidence: 99%